Impact of cash settlement on feeder cattle hedging risk - J.R. Mintert; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1989)
One of the principal motivations for the introduction of cash settlement in feeder cattle futures contracts was to reduce basis risk. This study examined expected changes in hedging risk attributable to the adoption of cash settlement. The estimates of cash settlement futures hedging risks were generally small than estimates of hedging risks using the physical-delivery futures. The reduction in hedging risk was greatest for feeder steers meeting futures contract weight specifications, but reductions were also common for other weight classes and for heifers.
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Feeder cattle; Market; Hedging